Interaction between gut microbiota and immunity in health and intestinal disease - Wang, Qishang; Meng, Qingguo; Chen, Yuchao; Liu, Yaxin; Li, Xinru; Zhou, Jinjie; Ma, Yuchu; Yu, Zihan; Chen, Xin (Frontiers in Immunology, 2025)
The gut microbiota plays a fundamental role in establishing and maintaining host immune homeostasis through dynamic, bidirectional interactions with the innate and adaptive immune systems. This review synthesizes current knowledge on how commensal microbes guide the development and function of the intestinal immune system. Conversely, we examine how the host immune system, including immunoglobulin A (IgA) and T-cell responses, actively shapes microbial composition and colonization resistance. Disruptions in this equilibrium (dysbiosis) are critically implicated in pathogenesis. We explore the dysbiosis-immune axis in inflammatory bowel diseases (IBD), irritable bowel syndrome (IBS), and colorectal cancer (CRC), highlighting how specific microbial taxa and their metabolites influence disease progression through immune modulation. Furthermore, we discuss how acute infectious insults model the breakdown of this mutualism.